Judiciário e autoritarismo : regime autoritário (1964-1985), democracia, usos e abusos da memória institucional - Schinke, Vanessa Dorneles (2015)
In order to reflect on the Judiciary Power role in the Brazilian democracy and its level of engagement with the constitutional project initiated in 1988, this work sought elements from popular statements of the official memory about the performance of the Judiciary Power during the authoritarian period. The investigation suggests that the silence of the institutional narrative about the last authoritarian period provides a privileged space to identify that the Judiciary has actively collaborated in maintaining the authoritarian project, according to the weapons available to it, levelling its exercise of its functions when needed by the authoritarian regime. The research problem is confronted with the silence produced by the official memory. Within this boundary, the hypothesis used was that the traits of independence, impartiality, fundamental rights defence and control of constitutionality were carved as required by the authoritarian regime, with no official historiography of the Judiciary recording those movements. The goal to adopt this conducting line is to indicate that the same structures can also be moved in within diametrically diverse political contexts. At the end, the instrument of the research hypothesis suggests the existence of a Judiciary, whose practices in democracy can be just as or more authoritarian as those performed in an authoritarian regime.